Funding Opera in the Changing Landscape: Should Opera Be Funded or Accepted as a Fading Culture in South Africa? - Yende, Sakhiseni Joseph (Research in Social Sciences and Technology- OpenED Network, 2024)
Opera is considered a significant part of cultural heritage in many societies. In the South African context, opera has a rich history and has contributed to the development of various art forms. Opera has continued to play a significant role in preserving and promoting cultural diversity in South Africa. Opera production contribute to the economy by creating jobs for artists, musicians, technicians, and other professionals. Additionally, opera events can attract tourism and boost local economies. Public funding for opera may be seen as an investment with economic returns. The purpose of this article is to examine the funding of opera in South Africa against the backdrop of a changing cultural landscape. It aims to investigate whether opera should continue to receive funding or if it should be accepted as a fading cultural form. Employing a qualitative approach, ten participants, including opera company managers and artists, share their perspectives through semi-structured interviews. Colaizzi's phenomenological data analysis method reveals key themes of financial viability, challenges, and opportunities. Findings were presented in themes and supported by quotes from research participants. Opera company managers and artists shared valuable insights into financial viability, challenges, and opportunities. Strategic collaborations, revenue diversification, and the pivotal role of public funding emerged as central themes. The findings shed light on the adaptive measures undertaken by stakeholders in response to the changing cultural and financial climate. The conclusion synthesises the key findings, emphasising the resilience of South African opera in the face of funding challenges. It underscores the importance of balancing financial support and cultural acceptance for sustained vitality. The study contributes to ongoing discussions on the intersection of funding, cultural relevance, and the future of opera in South Africa.